Containment and Mitigation Measures of COVID-19-A Scoping Review - Lim Kuang Kuay; Faizul Akmal Abdul Rahim; Fazila Haryati Ahmad; Ahzairin Ahmad; Halizah Mat Rifin; Mohd Shaiful Azlan Kassim; Muhd Hafizuddin Taufik Ramli; Nur Hamizah Nasaruddin; Jayvikramjit singh Manjit singh; Norsyamlina Che Abdul Rahim (Britain International for Academic Research (BIAR) Publisher, 2020)
The epidemic of Coronavirus Disease 2019 (Covid-19) in China and a number of countries had led to the Covid-19 pandemic declaration by WHO. The aim of this study is to assess the evidence and to report the effectiveness of Covid-19 containment and mitigation measures among the affected countries. A comprehensive search strategy was performed using the MESH terms of “Novel coronavirus,” “Novel coronavirus 2019”, “2019 nCoV”, “Covid-19”, “Wuhan coronavirus”, “SARS-CoV-2”, “Containment”, “Mitigation” and “Control”. After completion of the initial screening, 922 articles were excluded for the following reasons: the article did not meet the inclusion criteria (N = 862), the article was a duplicate (N = 60). The remaining 72 articles were screened at the full-text level. After full review for relevancy, 41 articles were excluded and a total of 31 articles were selected for scoping review. The two most successful countries that managed to control this pandemic were Hong Kong and South Korea. While, the United States of America (USA) and Brazil are the countries yet unable to significantly reduce the Covid-19 cases. The aggressiveness of government efforts and the compliance among the population are the main factors contributing to the effectiveness of the containment and mitigation measures implemented.